Southern African scorpion toxins: An overview - du Plessis, L.H.; Elgar, D.; du Plessis, J.L. (Toxicon (Oxford), 2008)
In southern Africa there are 130 species of scorpions and only a few species’ venom have been investigated to date. This review gives an overview of the research done on the venom of southern African scorpions and the toxins and peptides identified up to date. It also aims to highlight the enormous potential that lies in this field of research. Southern African scorpion toxins include four long-chain Na +-channel toxins, four short-chain α-K +-channel toxins ( α-KTx), three Ca 2+-channel toxins and also an insect-selective peptide active on K + and Cl − channels. Three antimicrobial peptides have also been isolated and characterized. All of these peptides are diverse not only in function and target but also in the species they are isolated from.